A propaganda do cigarro: estratégias publicitárias pós condenação do tabagismo no Brasil - Lobianco, Carolina Lopes (2018)
The main purpose of this master’s dissertation is the cigarette advertising debate in Bra-zil after the tobacco conviction. The industry advertising strategies used by USA and United Kingdom according to the first researches which linked tobacco and lung cancer are equally examined in this work, considering that most of them were adapted to the Brazilian case. The conviction of the tobacco industry in Brazil has only started after the Federal Constitution of 1988, when Brazilian Government has started to control the advertising of certain products like tobacco, alcoholic drinks, pesticides, medicines and theraphies.This present study does a brief history of the beginning of the tobacco industry in Brazil, concentrated in the cigarette advertising, and its developments after 1988.